O lugar do texto no ensino de língua portuguesa na EJA: por uma orientação prática e pedagógica da linguística textual - SIQUEIRA, Edivana Valéria Rosa (2018)
This work aims to address the teaching of Portuguese Language in the EJA and propose a pedagogical practice centered on the use of texts as a mechanism of meaningful learning, in light of the assumptions of Textual Linguistics, including its main phases, authors and current perspectives. This is an applied research of a qualitative nature. The Alto do Turu School, belonging to the municipality of São José de Ribamar - MA was the locus of the research, and had as investigated subjects, the students and the Portuguese Language teacher of the 7th and 8th years of the EJA of said school. Questionnaires were applied for diagnostic purposes and for the definition of intervention interventions. To materialize this research were elaborated and applied didactic sequences related to the grammatical contents that the subjects involved in the research reported having greater difficulty. The activities were based on reading, rewriting and producing texts of various types and genres. It was noticed the need to reformulate the teaching practices in the EJA, in a perspective of the inclusion of contents and notions pertinent to the interactional perspective of the language. For this, a product was constructed, materialized in a notebook of orientations composed by didactic sequences applied and other interventional and methodological suggestions on the grammatical categories studied during the period of application of the research. The said product is based on activities intermediated by the work with texts, based on the description of the linguistic phenomena related to the construction of the senses.